Polyurethane anti-fatigue floor mat material, preparation method and application thereof
By foaming the polyurethane fatigue-resistant floor mat with a composition of polyether polyol A, polymer polyol B and polyester ether polyol C, the problem of insufficient tensile strength and tear strength in the prior art is solved, and the effects of high tensile resistance, high tear strength and wear resistance are achieved, which extends the service life and expands the scope of application.
Patent Information
- Application Number
- CN202111583067.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-22
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-12-22
AI Technical Summary
The tensile strength and tear strength of existing polyurethane fatigue-resistant floor mats cannot be excellent at the same time, which limits its service life and scope of application.
Polyurethane anti-fatigue floor mats are made by foaming the composition of polyether polyol A, polymer polyol B and polyester ether polyol C. By introducing a special structure of polyester ether polyol C, the content of polar groups and intermolecular force in the molecular segment are increased.
The tensile strength, elongation of break and tear strength of the polyurethane fatigue-resistant floor mat are significantly improved, so that the density is 190-210 kg/m3, the surface hardness is 25-35, the tensile strength is 490-520 kPa, the elongation of break is 190-210%, and the tear strength is 8.0-11.0N/cm, which extends the service life and expands the scope of application.
Smart Images

Figure BDA0003426893020000041 
Figure BDA0003426893020000051 
Figure BDA0003426893020000052
Abstract
Description
Technical Field
[0001] The invention relates to a polyurethane anti-fatigue floor mat material, a preparation method and application thereof. Background Art
[0002] With the development of society and the improvement of people's living standards, people are paying more and more attention to their own health and relieving their own fatigue. One of the most common causes of physical fatigue is standing on hard and wet ground. This fatigue is mainly manifested in the neck, legs, and joints. However, these physical stresses and discomforts will eventually have a direct impact on the health and work efficiency of the staff. Muscle and joint contraction, sharp decrease in blood flow, feeling of pressure discomfort (the heart is forced to work under load, causing a large amount of energy loss in the body, a sharp decrease in work capacity, and varicose veins), heel and ankle pain, etc. According to research, 83% of the American workforce (industry) suffers from foot and calf pain, and 15% of these ailments are related to standing and walking for a long time. PU anti-fatigue floor mats can effectively help people get rid of this fatigue with their high rebound material, fatigue resistance, softness and comfort, professional anti-slip technology and other characteristics. They are currently widely used in entrance halls, living rooms, kitchens, bathrooms, bedrooms, assembly lines, white-collar offices, supermarket cashiers, doctors' operating rooms, etc. At present, the main materials of anti-fatigue floor mats on the market are rubber, EPE, PVC, XPE, EVA, PU, etc. Polyurethane (PU) anti-fatigue floor mats have significant advantages in terms of safety, environmental protection, and comfort. Traditional polyurethane anti-fatigue floor mats have poor tensile tearing and wear resistance, which greatly limits the service life and scope of use of anti-fatigue floor mats. Therefore, how to improve the tensile tearing of polyurethane anti-fatigue floor mats is particularly critical. In the prior art, in order to meet the performance requirements, the density of anti-fatigue floor mats is generally 200±10kg / m 3 , surface hardness 28-45, tensile strength greater than 400kPa, elongation at break greater than 100%, tear strength greater than 0.50N / mm.
[0003] Chinese patent CN 104622235A discloses a self-skinning anti-fatigue floor mat and its preparation process, including a floor mat body, the floor mat body is integrally formed of polyurethane, the floor mat body includes an upper surface layer, an inner core layer and a lower surface layer, the upper surface layer and the lower surface layer are both high-density polyurethane layers, and the inner core layer is a low-density polyurethane layer. The floor mat prepared by the invention has a tensile strength of 0.45Mpa, an elongation at break of 100%, and a tear strength of 0.50N / mm. The tensile strength and tear strength of the invention are not excellent enough.
[0004] Chinese patent CN 108383964A discloses a plant PU anti-fatigue floor mat, which contains 13-40 parts of plant polyether, 0-1 part of catalyst, 1-5 parts of foaming agent, 0.1-0.3 parts of plant amine, 1-2 parts of silicone oil, 7-33 parts of polyamine polyether, 0.1-0.3 parts of release agent, 0.1-0.3 parts of paint, 0.1-0.3 parts of color paste, 3-26 parts of liquefied MDI and 3-20 parts of isocyanate per 100 parts of the floor mat. However, the invention does not disclose the specific physical performance indicators of the prepared floor mat. Summary of the invention
[0005] One of the technical problems to be solved by the present invention is that the tensile strength and tear strength of polyurethane anti-fatigue mats in the prior art cannot be excellent at the same time, and a new polyurethane anti-fatigue mat is provided, which has the advantages of high tensile strength and high tear strength. The second technical problem to be solved by the present invention is to provide a preparation method of polyurethane anti-fatigue mats corresponding to the first technical problem to be solved. The third technical problem to be solved by the present invention is to provide an application of polyurethane anti-fatigue mats corresponding to the first technical problem to be solved.
[0006] In order to solve one of the above technical problems, the technical solution adopted by the present invention is as follows: a polyurethane anti-fatigue mat material, comprising the following components in parts by weight: polyether polyol A: 60-90 parts, polymer polyol B: 8-40 parts, polyester ether polyol C: 5-30 parts, isocyanate 35-60 parts, water: 0.6-2 parts, foaming agent: 7-20 parts, reaction catalyst: 0.5-1 part, foam stabilizer: 0.2-1 part, chain extender: 2-5 parts, pore opener: 1-5 parts, color paste: 0-2 parts, release agent: 0.1-0.3 parts, polyurethane in-mold paint: 0.1-0.3 parts; wherein the polyether polyol A is a polyether copolymer of ethylene oxide and propylene oxide with a molecular weight of 4000-8000 and at least one of glycerol, trimethylolpropane, ethanolamine or sorbitol as an initiator. The polyol has a primary hydroxyl content of ≥70%, an unsaturation of 0.01-0.2 mmol / g, and a functionality of 2-4; the polymer polyol B has a hydroxyl value of 22-27 mgKOH / g, a water content of ≤0.05%, a pH value of 5-8, a viscosity of ≤3000 mPa·s, and a solid content of 26-30%; the polyester ether polyol C has a molecular weight of 600-3000, a viscosity of 1000-2500 mps·s, and a functionality of 2-4; the chain extender is a non-amine small molecule alcohol compound containing two functional groups; the foam stabilizer is a polysiloxane-oxidized olefin block or graft copolymer; the reaction catalyst is a tertiary amine catalyst containing a hydroxyl group; the pore opening agent is a polyoxyolefin-polysiloxane copolymer; and the isocyanate is selected from at least one of toluene diisocyanate or carbodiimide modified isocyanate.
[0007] In the above technical scheme, preferably, the chain extender is selected from at least one of 1,4-butanediol, ethylene glycol, diethylene glycol or neopentyl glycol; the foam stabilizer is selected from at least one of B8681, B8715 or L5333; the blowing agent is selected from one of HCFC-141B or HFC-425; the cell opener is selected from one of CHE-350D, KF-28 or LK-3350; the isocyanate is selected from one of MDI-LL, BASF-103C or MDI-100L.
[0008] In the above technical solution, preferably, the reaction catalyst is selected from at least one of a foaming tertiary amine catalyst, a gel tertiary amine catalyst or a balanced tertiary amine catalyst.
[0009] In the above technical scheme, preferably, the foaming tertiary amine catalyst is selected from at least one of dimethylaminoethoxyethanol, trimethylhydroxyethylethylenediamine or N,N,N'-trimethyl-N'-hydroxyethylbisaminoethyl ether; the gel tertiary amine catalyst is selected from N,N-bis(dimethylaminopropyl)isopropanolamine or N-(dimethylaminopropyl)diisopropanolamine; and the balanced tertiary amine catalyst is selected from dimethylethanolamine.
[0010] In the above technical solution, preferably, the polyurethane in-mold paint is a single-component in-mold paint; the color paste is a polyether polyurethane color paste; and the release agent is a water-soluble release agent.
[0011] In the above technical solution, preferably, the preparation method of the polyester ether polyol C comprises the following steps:
[0012] (1) Putting multifunctional polyether polyol and dibasic acid anhydride into a reaction kettle, replacing the air in the reaction kettle with nitrogen for multiple times, keeping the pressure in the kettle at 0.01-0.4 MPa, raising the temperature, controlling the reaction temperature in the kettle to be 125-135° C., and the reaction time to be 2-4 hours;
[0013] (2) lowering the temperature in the reactor to 70-90° C.; adding a 0.2-0.5% by mass of a liquid caustic soda aqueous solution of a multifunctional polyether polyol to the reactor;
[0014] (3) at a negative pressure of -0.1 to -0.01 MPa, propylene oxide is passed into the reaction kettle; then the reaction temperature is controlled to be 110 to 120° C.; the reaction pressure is 0.01 to 0.4 MPa; the reaction time is 5 to 8 hours; and a crude ether of polyester ether polyol is obtained;
[0015] (4) lowering the temperature in the kettle to 80-85° C., adding the magnesium silicate composite adsorbent under stirring; after stirring for 40-90 minutes, raising the temperature in the kettle to 110-120° C., dehydrating for 2-4 hours, and obtaining the final product, polyester ether polyol.
[0016] In the above technical scheme, preferably, the multifunctional polyether polyol is prepared by using at least one of propylene glycol, diethylene glycol, 1,4-butanediol, glycerol, sorbitol and pentaerythritol as an initiator, and has a molecular weight of 200 to 2000; the dibasic acid anhydride is selected from at least one of phthalic anhydride, isophthalic anhydride and maleic anhydride; the molar ratio of the multifunctional polyether polyol to the dibasic acid anhydride is 1:1 to 2; the molar ratio of the multifunctional polyether polyol to propylene oxide is 1:2 to 5.
[0017] To solve the second of the above technical problems, the technical solution adopted by the present invention is as follows.
[0018] A method for preparing the aforementioned polyurethane anti-fatigue floor mat material comprises the following steps:
[0019] 1) Raise the mold temperature to 40-50°C and evenly spray 0.1-0.3 parts of release agent on the inner surface of the mold;
[0020] 2) After the release agent is cured to form a film on the mold surface, 0.1 to 0.3 parts of polyurethane in-mold paint is evenly sprayed on the inner surface of the lower mold;
[0021] 3) Add 60-90 parts of polyether polyol A, 8-40 parts of polymer polyol B, 5-30 parts of polyester ether polyol C, 35-60 parts of isocyanate, 0.6-2 parts of water, 7-20 parts of foaming agent, 0.5-1 part of reaction catalyst, 0.2-1 part of foam stabilizer, 2-5 parts of chain extender, 1-5 parts of cell opener, 0-2 parts of color paste into container A by weight, stir evenly at a stirring speed of 2000-3000 rpm, and control the material temperature at 20-30° C. to obtain material I;
[0022] 4) Add 35 to 60 parts by weight of isocyanate into container A, and stir quickly and evenly for 4 to 6 seconds to obtain a mixture II at a stirring speed of 2000 to 5000 rpm;
[0023] 5) Rapidly inject the mixed material II into the mold, close and lock the mold, keep the mold for 6 to 10 minutes, then open the mold, take out the product, and mature it at room temperature for 2 to 4 days to obtain the polyurethane anti-fatigue mat.
[0024] In the above technical solution, preferably, the density of the polyurethane anti-fatigue mat is 190-210 kg / m 3 , Shore C surface hardness is 25-35, tensile strength is 490-520kPa, elongation at break is 190-210%, tear strength is
[0025] 8.0~11.0N / cm.
[0026] To solve the third of the above technical problems, the technical solution adopted by the present invention is as follows.
[0027] A floor mat prepared from the aforementioned polyurethane anti-fatigue floor mat material is used in indoor places such as hotels, office buildings or kitchens.
[0028] The invention provides a new polyurethane anti-fatigue mat material. A polyurethane anti-fatigue mat with high tensile strength and high tear strength is prepared by foaming a polyol composition of polyether polyol A, polymer polyol B and polyester ether polyol C. The polyester ether polyol C with a special structure is introduced to greatly increase the content of polar groups in the molecular chain segments and the intermolecular force, thereby effectively improving the tensile tearing performance and wear resistance of the anti-fatigue mat, extending the service life of the anti-fatigue mat and expanding its application range, so that the density of the prepared polyurethane anti-fatigue mat is 190-210 kg / m 3 , Shao C surface hardness is 25-35, tensile strength is 490-520kPa, elongation at break is 190-210%, tear strength is 8.0-11.0N / cm, which can be applied to most indoor places and achieved good technical effects. DETAILED DESCRIPTION
[0029] Table 1 List of raw materials – additives
[0030]
[0031]
[0032] Table 2 Raw materials list – main raw materials
[0033]
[0034] The polyester ether polyol C used in the embodiment is prepared by the following preparation method:
[0035] Add 1000g CHE-210 and 196g phthalic anhydride to a reaction kettle equipped with a stirring device, replace the air in the kettle with nitrogen, keep the kettle in a vacuum state, and heat to 130°C for reaction for 3 hours. Cool down to 85°C, add 2.1g of 50% potassium hydroxide aqueous solution by mass percentage, and then pass 116g PO into the kettle under negative pressure of -0.05Mpa, react at 115°C for 6 hours, and discharge the material. Place the material in a three-necked flask with a stirring device, stir at 85°C and add 7.9g of magnesium silicate composite adsorbent, wherein the magnesium silicate composite adsorbent is a mixture of magnesium silicate A and magnesium silicate B, magnesium silicate A 2.0g, magnesium silicate B 5.9g; the particle size of magnesium silicate A is 45μm, and the specific surface area is 100m 2 / g, pore volume 0.06cm3 / g; the particle size of magnesium silicate B is 110μm and the specific surface area is 32m 2 / g, pore volume 0.68cm 3 / g; one hour later, the temperature was gradually raised to 115°C and dehydrated for 3 hours to obtain polyester ether polyol-1 with a molecular weight of 1305, an acid value of 0.17 mgKOH / g and a viscosity of 1260 mpa·s.
[0036] [Example 1]
[0037] (1) Raise the mold temperature to 45°C and evenly spray 0.3 parts of release agent 3011B on the inner surface of the mold;
[0038] (2) After the release agent is cured to form a film on the mold surface, 0.3 parts of polyurethane in-mold paint 5UC-440T05B is evenly sprayed on the inner surface of the lower mold;
[0039] (3) Add 86 parts of CHE-330N, 9 parts of CHP-H30, 5 parts of polyether polyol C, 4 parts of EG, 1 part of BDO, 0.5 parts of triethylenediamine, 0.2 parts of DMEA, 0.1 parts of A300, 0.1 parts of B8715, 0.4 parts of B8681, 3 parts of CHE-350D, 1.2 parts of water, 11 parts of HCFC-141B, and 2 parts of color paste 5UC-4406T02B into container A by weight, and stir evenly at a stirring speed of 2500 rpm and a material temperature of 25° C. to obtain material I;
[0040] (4) Add 51 parts by weight of isocyanate LL into container A, and stir rapidly and evenly for 5 seconds to obtain a mixture II at a stirring speed of 3000 rpm;
[0041] (5) The mixed material II is rapidly injected into the mold, the mold is locked, and the mold is maintained for 7 minutes. Then, the mold is opened, the product is taken out, and it is aged at room temperature for 3 days to obtain a polyurethane anti-fatigue floor mat.
[0042] [Examples 2 to 7 and Comparative Examples 1 to 3]
[0043] Examples 2 to 4 are carried out according to the steps of Example 1, with the only difference being the type of reaction raw materials, the type of catalyst, the raw material ratio, the reaction time and the temperature, as shown in Table 3. The conventional physical property test data of the prepared polyurethane anti-fatigue floor mat with high tensile strength and high tear strength are shown in Table 5.
[0044] Examples 5 to 7 and Comparative Examples 1 to 3 were carried out according to the steps of Example 1, with the only difference being the types of reaction raw materials, catalyst types, raw material ratios, reaction times and temperatures, as shown in Table 4. The conventional physical property test data of the prepared polyurethane anti-fatigue floor mat with high tensile strength and high tear strength are shown in Table 5.
[0045] Table 3 Weight parts of raw materials of each component in Examples 1 to 4
[0046]
[0047]
[0048] Table 4 Weight percentage of raw materials of each component in Examples 5 to 7 and Comparative Examples 1 to 3
[0049]
[0050]
[0051]
[0052] Table 5 Performance test data of polyurethane anti-fatigue floor mats prepared in Examples 1 to 7 and Comparative Examples 1 to 3
[0053]
[0054]
[0055] Comparative Example 1 shows the performance index of conventional anti-fatigue floor mats on the market, and Comparative Examples 2 to 3 are based on the conventional anti-fatigue floor mat formula and are adjusted to improve tensile strength, elongation at break and tear strength. The results show that while the tensile strength is improved, the tear strength and elongation at break are significantly reduced, the Shao C surface hardness is also significantly improved, and the comfort is poor.
[0056] It can be seen from Examples 1 to 7 that the tear strength of the polyurethane anti-fatigue floor mat of the present invention can be as high as 10.5 N / cm, and the tensile strength is 510 kPa. Compared with Comparative Example 1, while maintaining the original hardness and density, the tensile strength, elongation at break and tear strength are greatly improved.
[0057] The above content introduces in detail the preparation method of a polyurethane anti-fatigue mat with high tensile strength and high tear strength provided by the present invention. The embodiments in this article illustrate the principle and implementation method of the present invention. The introduction of the above embodiments is only for understanding the core idea of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the field shall make modifications to the present invention without departing from the principle of the present invention, and the modifications shall fall within the protection scope of the claims.
Claims
1. A polyurethane anti-fatigue floor mat material, composed of the following components in parts by weight: Polyether polyol A: 60-90 parts, polymer polyol B: 8-26 parts, polyester ether polyol C: 5-30 parts, isocyanate 35-60 parts, water: 0.6-2 parts, foaming agent: 7-20 parts, reactive catalyst: 0.5-1 parts, foam stabilizer: 0.2-1 parts, chain extender: 4-5 parts, cell opener: 1-5 parts, color paste: 0-2 parts, mold release agent: 0.1-0.3 parts, polyurethane in-mold paint: 0.1-0.3 parts; wherein, polyether polyol A is a polyether polyol of ethylene oxide-propylene oxide copolymer with at least one of glycerol, trimethylolpropane, ethanolamine or sorbitol as an initiator, a molecular weight of 4000-8000, a primary hydroxyl content of ≥70%, an unsaturation of 0.01-0.2 mmol / g, and a functionality of 2-4; the hydroxyl value of polymer polyol B is 22-27 mgKOH / g, water content ≤0.05%, pH value 5-8, viscosity ≤3000mPa·s, solid content 26-30%; the molecular weight of polyester ether polyol C is 600-3000, the viscosity is 1000-2500mps·s, and the functionality is 2-4; the reaction catalyst is a tertiary amine catalyst containing hydroxyl groups; the chain extender is selected from at least one of 1,4-butanediol, ethylene glycol, diethylene glycol or neopentyl glycol; the foam stabilizer is selected from at least one of B8681, B8715 or L5333; the foaming agent is selected from one of HCFC-141B or HFC-425; the cell opener is selected from one of CHE-350D, KF-28 or LK-3350; the isocyanate is selected from one of MDI-LL, BASF-103C or MDI-100L; The preparation method of the polyester ether polyol C comprises the following steps: (1) Put multifunctional polyether polyol and dibasic acid anhydride into the reactor, replace the air in the reactor with nitrogen several times, keep the pressure in the reactor at 0.01-0.4Mpa, increase the temperature, and control the reaction temperature in the reactor at 125-135 o C, reaction time is 2 to 4 hours; (2) Lowering the temperature in the reactor to 70-90°C; adding a 0.2-0.5% aqueous solution of liquid alkali to the reactor; (3) Propylene oxide is passed into the reactor under a negative pressure of -0.1 to -0.01 MPa; the reaction temperature is then controlled to be 110 to 120°C; the reaction pressure is 0.01 to 0.4 MPa; the reaction time is 5 to 8 hours; and a crude ether of polyester ether polyol is obtained; (4) The temperature in the kettle is lowered to 80-85°C, and the magnesium silicate composite adsorbent is added under stirring; after stirring for 40-90 minutes, the temperature in the kettle is raised to 110-120°C, and dehydration is carried out for 2-4 hours to obtain the final product, polyester ether polyol.
2. The polyurethane anti-fatigue floor mat material according to claim 1, characterized in that: The reaction type catalyst is selected from at least one of a foaming type tertiary amine catalyst, a gel tertiary amine catalyst or a balanced tertiary amine catalyst.
3. The polyurethane anti-fatigue floor mat material according to claim 2, characterized in that: The foaming tertiary amine catalyst is selected from at least one of dimethylaminoethoxyethanol, trimethylhydroxyethylethylenediamine or N,N,N'-trimethyl-N'-hydroxyethylbisaminoethyl ether; the gel tertiary amine catalyst is selected from N,N-bis(dimethylaminopropyl)isopropanolamine or N-(dimethylaminopropyl)diisopropanolamine; and the balanced tertiary amine catalyst is selected from dimethylethanolamine.
4. The polyurethane anti-fatigue floor mat material according to claim 1, characterized in that: The polyurethane in-mold paint is a single-component in-mold paint; the color paste is a polyether polyurethane color paste; and the release agent is a water-soluble release agent.
5. A method for preparing the polyurethane anti-fatigue floor mat material according to claim 1, comprising the following steps: (1) Raise the mold temperature to 40-50°C and evenly spray 0.1-0.3 parts of release agent on the inner surface of the mold; (2) After the release agent is cured to form a film on the mold surface, 0.1 to 0.3 parts of polyurethane in-mold paint is evenly sprayed on the inner surface of the lower mold; (3) Add 60-90 parts of polyether polyol A, 8-26 parts of polymer polyol B, 5-30 parts of polyester ether polyol C, 0.6-2 parts of water, 7-20 parts of foaming agent, 0.5-1 part of reaction catalyst, 0.2-1 part of foam stabilizer, 4-5 parts of chain extender, 1-5 parts of cell opener and 0-2 parts of color paste to container A by weight, stir evenly at a stirring speed of 2000-3000 rpm and control the material temperature at 20-30°C to obtain material I; (4) Add 35 to 60 parts by weight of isocyanate into container A and stir rapidly and evenly for 4 to 6 seconds at a stirring speed of 2000 to 5000 rpm to obtain a mixture II; (5) Rapidly inject the mixed material II into the mold, close and lock the mold, keep the mold for 6 to 10 minutes, then open the mold, take out the product, and mature it at room temperature for 2 to 4 days to obtain a polyurethane anti-fatigue floor mat.
6. The method for preparing the polyurethane anti-fatigue floor mat material according to claim 5, characterized in that: The density of the polyurethane anti-fatigue mat is 190-210 kg / m 3 , Shao C surface hardness is 25-35, tensile strength is 490-520kPa, elongation at break is 190-210%, and tear strength is 8.0-11.0N / cm.
7. A floor mat made from the polyurethane anti-fatigue floor mat material according to claim 1, which is used in hotels, office buildings or kitchens.
Citation Information
Patent Citations
Self-skinning anti-fatigue floor mat and production process thereof
CN104622235A
Plant PU anti-fatigue ground mat
CN108383964A
Polyurethane composition for car steering wheel and preparation method of polyurethane composition
CN108047422A
Environment-friendly polyurethane football toy composition and preparation method thereof
CN108047423A
Low ethylene oxide / high primary hydroxyl content polyether-ester polyols and polyurethane foams based thereon
US4487853A